Marine Biosecurity Crisis Decision-Making: Two Tools to Aid “Go”/“No Go” Decision-Making - Campbell, Marnie L.; Leonard, Kaeden; Primo, Carmen; Hewitt, Chad L. (Frontiers in Marine Science, 2018)
Determining if a newly detected marine species is introduced to an area is an important first step when considering if control or eradication should be attempted. This step is often challenging, especially when data and introduced species expertise is limited: yet decisions about responding to a new invasion needs to occur in a timely manner. The crux is that biosecurity crisis decisions are often made in a vacuum. To improve this process, we consider expanded criteria to determine if a species is native, cryptogenic or introduced and outline application in a rapid response approach that uses a non-probabilistic decision tree to support decision makers. Effective use of the rapid response decision-tree and species criteria requires a multi-disciplinary approach drawing upon biology (taxonomy, phylogeny, genetics, ecology, biogeography) and monitoring. We assessed the expanded criteria against 213 bryozoan species present in Australian waters. A multivariate evaluation highlighted that a weight of evidence approach using the expanded criteria was successful in differentiating between native and introduced status. Our assessment highlighted that five criteria provide a high level of congruence with heuristic assignments, and provide a precautionary assignment of species' status by reducing mis-classifications of introduced species as native species (Type I error) in comparison to the original criteria. However, differentiating between introduced and cryptogenic species remains problematic, especially when using the original criteria. We highlight the critical need for taxonomic identification, appropriate application of assigning cryptogenic status, and monitoring requirements to enable use of the criteria in a rapid response context. Using both the rapid response decision tree and the criteria provides a quantifiable mechanism to aid decision-makers in deciding whether to respond to a marine species introduction.